Child maltreatment characteristics as predictors of heterogeneity in internalizing symptom trajectories among children in the child welfare system. (October 2017) - Yoon, Susan
Abstract: This study investigated heterogeneity in the developmental trajectories of internalizing symptoms among 541 children who were involved with the child welfare system and examined child maltreatment characteristics, including types, level of harm, and timing, as predictors of internalizing trajectory patterns. Secondary longitudinal research was conducted using data from the National Survey of Child and Adolescent Well-Being-I, collected from 1999 to 2007 in the United States. Three distinct trajectory groups were identified: high–decreasing; low–increasing; and low–stable Sexual abuse, emotional abuse, neglect, and more severe levels of harm from maltreatment predicted membership in two maladaptive groups compared to the low–stable group. The findings of the study suggest the importance of providing a thorough assessment of the type and severity of maltreatment experiences and continued monitoring of internalizing symptoms for children with child welfare involvement.